x2 - x - 3 = 0
x2 - 3x - 1 = 0
x2 - 3x - 3 = 0
x2 + 3x - 1 = 0
Correct answer is B
Given; y = x2 - x - 2, y = 2x - 1
Using y = y, gives
x2 - x - 2 = 2x - 1
x2 - 3x - 2 + 1 = 0
therefore, x2 - 3x - 1 = 0
If events X and Y are mutually exclusive, . P(X) = 1/3 and P(Y) = 2/5, P(X∩Y) is ...
Find the range of values of x which satisfy the inequalities 4x - 7 ≤ 3x and 3x - 4 ≤ ...
A sequence is given by 212,5,712,..... if the nth term is 25, find n...
Which of the following is a measure of dispersion? ...
Find the range of 1/6, 1/3, 3/2, 2/3, 8/9 and 4/3 ...
Given that p:q = 13:12 and q:r = 25, find p:r...
Two lines PQ and ST intersect at 75°. The locus of points equidistant from PQ and ST lies on the...